Independent Effect of Ethnicity on Glycemia in South Asians and White Europeans - Mostafa, Samiul A. (American Diabetes Association, 2012)
OBJECTIVE: HbA(1c) levels are higher in most ethnic groups compared with white Europeans (WEs) independent of glycemic control. This comparison has not been performed between South Asians (SAs) and WEs. We analyzed the independent effect of ethnicity on HbA(1c) and fasting and 2-h plasma glucose (FPG and 2hrPG, respectively) between these groups. RESEARCH DESIGN AND METHODS: Analysis of the ADDITION-Leicester study, in which 4,688 WEs and 1,352 SAs underwent oral glucose tolerance testing, HbA(1c), and other risk factor measurements. RESULTS: Significant associations with HbA(1c) included ethnicity, FPG, 2hrPG, and homeostasis model assessment of β-cell function (P < 0.001); age and sex (P < 0.01); and fasting insulin and potassium (P < 0.05). After adjusting for these and other risk factors, SAs demonstrated higher HbA(1c) (6.22 and 6.02%, mean difference 0.20%, 0.10–0.30, P < 0.001), FPG (5.15 and 5.30 mmol/L, mean difference 0.15 mmol/L, 0.09–0.21, P < 0.001), and 2hrPG (5.82 and 6.57 mmol/L, mean difference 0.75 mmol/L, 0.59–0.92, P < 0.001) compared with WEs, respectively. CONCLUSIONS: HbA(1c), FPG, and 2hrPG levels were higher in SAs independent of factors affecting glycemic control.